2015
DOI: 10.1177/0194599815621557
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Gastroesophageal Reflux

Abstract: In this analysis of a national database defining the 3 most prioritized diagnoses, GER is independently associated with OSA, with double the odds of concurrent occurrence, even while controlling for potentially related conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…Gastroesophageal reflux disease (GERD) is more common in patients with OSA . Increased GERD in OSA is likely due to more frequent transient lower oesophageal sphincter relaxations …”
Section: To What Degree Do Comorbidities Contribute To Difficult Asthma?mentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is more common in patients with OSA . Increased GERD in OSA is likely due to more frequent transient lower oesophageal sphincter relaxations …”
Section: To What Degree Do Comorbidities Contribute To Difficult Asthma?mentioning
confidence: 99%
“…A recent study expanded the relationship between GER and OSA to a population‐based level and showed that GER is independently associated with OSA. A significant positive relationship between GER and OSA has been recognized in a national database, with OSA defined on the basis of the International Classification of Diseases, 9th edition (ICD‐9). The strongest relationship was seen when using the strictest definitions of GER and OSA in a study that was performed by 24‐h pH monitoring and nocturnal PSG.…”
Section: Is There Any Causal Relationship Between Gerd and Osa?mentioning
confidence: 99%
“…1 Laryngopharyngeal reflux (LPR) is an extraesophageal manifestation of GERD that may be present in up to 10% of patients presenting for ambulatory otolaryngology visits. 2 Typical symptoms that have been attributed to LPR include globus sensation, laryngospasm, throat clearing, and hoarseness. Moreover, it has been postulated that mucosal inflammation due to LPR may extend beyond the larynx and oropharynx to the nasopharynx and nasal cavity, contributing to the pathogenesis of sinonasal diseases.…”
Section: Invited Commentarymentioning
confidence: 99%